Spatula: Efficient cross-camera video analytics on large camera networks - Jain, Samvit; Zhang, Xun; Zhou, Yuhao; Ananthanarayanan, Ganesh; Jiang, Junchen; Shu, Yuanchao; Bahl, Victor; Gonzalez, Joseph (ACM/IEEE Symposium on Edge Computing (SEC 2020), 2020)
Cameras are deployed at scale with the purpose of searching and tracking objects of interest (e.g., a suspected person) through the camera network on live videos. Such cross-camera analytics is data and compute intensive, whose costs grow with the number of cameras and time. We present Spatula, a cost-efficient system that enables scaling cross-camera analytics on edge compute boxes to large camera networks by leveraging the spatial and temporal cross-camera correlations. While such correlations have been used in computer vision community, Spatula uses them to drastically reduce the communication and computation costs by pruning search space of a query identity (e.g., ignoring frames not correlated with the query identity’s current position). Spatula provides the first system substrate on which cross-camera analytics applications can be built to efficiently harness the cross-camera correlations that are abundant in large camera deployments. Spatula reduces compute load by 8.3× on an 8-camera dataset, and by 23 × −86× on two datasets with hundreds of cameras (simulated from real vehicle/pedestrian traces). We have also implemented Spatula on a testbed of 5 AWS DeepLens cameras.